Variabilidad espacial de la salud mental en Aragón y análisis de su asociación con el nivel socioeconómico: deterioro cognitivo leve y demencia: Reseña de tesis doctoral - Rabanaque Hernández, Isabel (Geographicalia, 2022)
This is a summary of a retrospective study that analyzed the possible differences between the Basic Health Areas of Aragon as a geographical unit of analysis, on the one hand, in relation to socioeconomic level, and, on the other, in terms of the frequency of mild cognitive impairment. and dementia. Likewise, the possible relationship between socioeconomic level and frequency of the diseases described has been investigated.